(untitled) (Revista Sistemas de Producción Agroecológicos, 2016)
The development in the production of guinea pig (Cavalia porcellus), as an alternative source of protein for the population, is an initiative that has been gaining strength in Colombia; considering that the species Brachiaria grasses, represent a source of fiber and energy for the tropics, its inclusion in diets for C. porcellus is limited by the lack of information on its nutritional value and digestive harnessing in these animals, therefore, the objective of this study was to determine the nutritional value and digestibility coefficients of dry matter (DM), crude protein (CP), fat (GR) and crude fiber (CF), and estimate the nitrogen-free extract (ENN), percentage of total digestible nutrients (TDN), gross energy (Mcal/kg MS) (EB), digestible ( ED) and metabolic (EM). The forages and treatments used were: (Brachiaria hybrid cv. mulato (T1), Brachiaria decumbens cv. amargo (T2), Brachiaria brizantha cv. toledo (T3) and Brachiaria brizantha cv. marandú (T4). For the experiment twelve creole male Cavalia porcellus were used, with an average weight of 778 ± 10 g, installed in metabolic cages, distributed in a completely randomized design with four treatments, four species of Brachiaria and three replicates each one. The amount of forage consumed ad libitum was weighty, and also, they were collected and weighed feces for six days, to later analyze them in the laboratory, in order to estimate their digestibility coefficients and energy distribution. Digestibility coefficients of MS were higher (P<0.05) for B. decumbens and B. brizantha cv marandú (0.80 and 0.88). Likewise, the digestibility coefficients of CP, GR, CF, ENN and EB were higher (P<0.05) for these same fodder, observing, the highest ratio in CP of B. brizantha cv marandú (0.90) and the lowest in CF of B. brizantha cv toledo (0.66). B. decumbens was the best forage profiteer by C. porcellus due to lower fecal energy (EF) wasted (15.5%), leaving more energy for metabolic functions compared with other forages, being its EF 25.4, 21.4 and 22.6% for the B. híbrida cv. mulatto grass, B. brizantha cv. toledo and B. brizantha cv. marandú respectively. The digestible energy and metabolic was higher in B. decumbens despite its lower content PC (6%) compared to B. brizantha cv. marandú (7.8%). C. porcellus, grasses, digestibility, lesser species.